Ring-Opening of Donor-Acceptor Cyclopropane Diester for the Synthesis of Oxime Esters and 2,3-Dihydroazete Ester - Yadav, Neeraj; Verma, Kritika; Das, Arnab; Kaur, Navpreet; Banerjee, Prabal (Synthesis, 2024)
A simple and efficient approach for the synthesis of privileged oxime esters by employing donor-acceptor cyclopropane diesters (DACs) as one of the potential precursors is reported. The strategy involves Lewis acid catalyzed ring-opening of DACs, resulting in an open-chain intermediate followed by the base-mediated construction of the corresponding oxime esters in a one-pot reaction. Moreover, the process also features the synthesis of diethyl 4-(4-methoxyphenyl)azete-2,2(3H)-dicarboxylate.
Keywords: donor-acceptor cyclopropanes; zwitterionic compound; oxime esters; one-pot synthesis; bioactive compounds